SYSTEMATIC LITERATURE REVIEW STRATEGI DALAM MENGHADAPI TANTANGAN STRUKTUR PASAR MONOPOLI DI ERA DIGITAL - Endra, Sumarta; Widiasari, Zulfeni; Zefriyenni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study provides a Systematic Literature Review (SLR) on strategies to address the challenges of monopoly market structures in the digital era. The study follows the PRISMA guidelines and collects articles published between 2015 and 2025 from Scopus and Google Scholar databases. Through a rigorous selection process, eleven of the most relevant articles were chosen for further evaluation. The study finds that monopoly markets in the digital era face complex issues due to the tension between antitrust regulations and the need for innovation; overly strict antitrust policies may hinder the innovation incentives of dominant firms. With the growth of the digital platform economy, these dynamics become increasingly complicated by the emergence of “data monopolies,” which dominate markets through the use of algorithms and information. Using VOSviewer, we conducted a bibliometric analysis and identified four main research clusters: regulatory model development, management strategies, digital market dynamics, and sectoral applications. The study demonstrates that effectively managing monopoly markets requires innovative regulatory approaches that not only focus on limiting monopoly power but also encourage collaboration between governments, businesses, and academics in developing evidence-based policies. This research provides both theoretical and practical contributions to market management policymaking that balances economic growth, consumer protection, and the promotion of healthy competition in an increasingly complex digital era.